Floral depravity - Allen, Beverly (Novelist) (Allen, Beverly (Novelist) Bridal bouquet shop mystery, 2015)
As the co-owner of the Rose in Bloom Flower Shop, Audrey knows how to put together unique wedding bouquets, but this one takes the cake. The daughter of a local historian is getting married in a medieval-themed, hand-fasting ceremony, and Audrey is responsible for providing period-accurate blooms. But making sure she gets her roses right turns out to be the least of Audrey's problems. Shortly after the vows are exchanged, the father of the groom suddenly drops dead. When Audrey discovers the man's death stems from monkshood poisoning, it's a clear-cut case of murder. Now, faced with a suspect list that rivals the guest list, Audrey needs to root out the toxic killer.